[TEX]\frac{sin^3(x)sin(3x)+cos^3(x)cos(3x)}{tan(x-\frac{pi}{6})tan(x+\frac{pi}{3})}=\frac{-1}{8}[/TEX]
ta có :
+) bạn cứ biến đổi mẫu số bình thường thì được mẫu = -1 :|
thay vào pt, pt trở thành:
[TEX]sin^3 x.sin3x+cos^3 x.cos3x = \frac{1}{8}[/TEX]
\Leftrightarrow [TEX]sin^2 x.sinx.sin3x+cos^2 x.cosx.cos3x = \frac{1}{8}[/TEX]
\Leftrightarrow [TEX]\frac{1}{2}sin^2 x.(cos2x-cos4x)+\frac{1}{2}cos^2 x(cos4x+cos2x) = \frac{1}{8}[/TEX]
\Leftrightarrow [TEX]sin^2 x.cos2x-sin^2 x.cos4x+cos^2 x.cos4x+cos^2 x.cos2x =\frac{1}{4}[/TEX]
\Leftrightarrow [TEX]cos4x.(cos^2-sin^2)+cos2x(cos^2 x+sin^2 x) = \frac{1}{4}[/TEX]
\Leftrightarrow [TEX]cos4x.cos2x+cos2x = \frac{1}{4}[/TEX]
\Leftrightarrow [TEX]\frac{1}{2}.(cos6x+cos2x)+cos2x = \frac{1}{4}[/TEX]
\Leftrightarrow [TEX]cos6x+3cos2x-\frac{1}{2} =0[/TEX]
\Leftrightarrow [TEX]4cos^3 2x-3cos2x+3cos2x-\frac{1}{2} = 0[/TEX]
tự giải, xem coi mình có viết nhầm không nhé, nhớ lấy đk :|